« Revêtir l’homme nouveau ». Fragments d’une méditation spirituelle dans les Lettere d’Antonio Minturno (Venise, 1549) - Maria Cristina Panzera (Les Cahiers de Framespa)
Neapolitan humanist Antonio Minturno published his book of Letters in Venice in 1549. This work has not been studied yet from the point of view of the Italian reformation movement in Renaissance. His letters’ collection is part of the tradition of familiar letters and shows the many facets of the author’s commitment to his role as a church man, writer and secretary in the service of the powerful Pignatelli family, especially the Duke Ercole whom Charles Quint had raised to the rank of Vice-King of Sicily. The letters about young Bacchini’s conversion to religious life, becaming a hermit brother in 1534, contain many spiritual accents, which invite us to examine the author’s relations with the Neapolitans circles marked by the influence of Valdes.